1992
DOI: 10.1093/cercor/2.5.375
|View full text |Cite
|
Sign up to set email alerts
|

Varieties of Functional Deficits in Prosopagnosia

Abstract: Prosopagnosia is a neurologically based deficit characterized by the inability to recognize faces of known individuals in the absence of severe intellectual, perceptual, and memory impairments. The nature of the underlying disturbance was investigated in three patients in an attempt to identify the structural and functional levels at which the processing of faces breaks down, the relation between prosopagnosia and associated deficits, and the specificity of the prosopagnosic disturbance. The breakdown of face … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
165
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(180 citation statements)
references
References 0 publications
15
165
0
Order By: Relevance
“…Results from neuropsychological studies suggest face processing may dissociate from long-term object expertise. After brain lesions causing prosopagnosia, WJ acquired a flock of sheep and became capable of recognizing sheep faces better than normal controls and scored best among a group of sheep farmers (46), whereas RM retained his superior ability to recognize car makes and models (47). Florence and another acquired prosopagnosic could successfully discriminate bodies, a category that generates substantial inversion effects and is relatively wellmatched to faces in terms of visual exposure and perceptual experience (48).…”
Section: Implications For the Expertise Hypothesis And For The Greeblmentioning
confidence: 99%
“…Results from neuropsychological studies suggest face processing may dissociate from long-term object expertise. After brain lesions causing prosopagnosia, WJ acquired a flock of sheep and became capable of recognizing sheep faces better than normal controls and scored best among a group of sheep farmers (46), whereas RM retained his superior ability to recognize car makes and models (47). Florence and another acquired prosopagnosic could successfully discriminate bodies, a category that generates substantial inversion effects and is relatively wellmatched to faces in terms of visual exposure and perceptual experience (48).…”
Section: Implications For the Expertise Hypothesis And For The Greeblmentioning
confidence: 99%
“…Yin, 1969;Valentine 1988;Rossion and Gauthier 2002), a visual preference for facelike stimuli in human neonates (Johnson and Morton 1991;see also Turati et al 2002), and selective impairments of face and object recognition in neurological patients (prosopagnosia and visual agnosia) (e.g. Sergent and Signoret 1992;Farah 1996;Moscovitch et al 1997). Recordings of human event-related potentials showed a different topography to face (including human and animal faces) and non-face object or scene stimuli in the N170 time window (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Elecrtophysiology and brain imaging studies further suggested a distinct neuroanatomical region in cerebral cortex associated with the cortical processing of faces (face-selective neurons in monkey inferotemporal cortex, fusiform face area in human cortex) (e.g. Sergent et al 1992;McCarthy et al 1997;Tanaka 1997;Tsao et al 2003). However, this view is recently challenged by some brain imaging studies suggesting that faces are processed by a domain-general system for fine-grained, exemplar-level object perception but probably at different level of recognition or different degree of perceptual expertise (Gauthier et al 1999(Gauthier et al , 2000Tarr and Cheng 2003).…”
Section: Introductionmentioning
confidence: 99%
“…When prosopagnosia occurs in normal adults as a consequence of brain damage, it is most often associated with lesions in the occipito-temporal brain regions (1)(2)(3)(4)(5)(6). In other cases, there is no evidence of brain damage, and the exact etiology of face recognition deficits is unknown (7)(8)(9).…”
mentioning
confidence: 99%